2006
DOI: 10.1143/jjap.45.8883
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Favorable Properties of Compound RF Discharge Plasmas with a Tapered Shape Hollow Cathode Compared with a Plane Cathode

Abstract: An experimental investigation on the characteristics of compound RF discharge plasmas with a tapered shape hollow-cathode (HC) compared with a plane cathode is presented for the development of processing plasma. Dense plasmas are shown to be generated in the wide range of working pressures, 3< p<90 Pa. It is clarified that the higher RF power yields the greater HC effect to increase the ratio of electron density with the HC to that without it. The HC effect is shown to work well for decreasing the self-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
1
11
0
Order By: Relevance
“…This trend is probably due to the slowdown of electrons by collisions that becomes more frequent since the free path length is reduced as the gas pressure is increased. A similar behavior was observed by Yambe et al in a comparative study between tapered shape hole and plane cathode [13].…”
Section: Self-bias Voltage (V DC )supporting
confidence: 87%
See 1 more Smart Citation
“…This trend is probably due to the slowdown of electrons by collisions that becomes more frequent since the free path length is reduced as the gas pressure is increased. A similar behavior was observed by Yambe et al in a comparative study between tapered shape hole and plane cathode [13].…”
Section: Self-bias Voltage (V DC )supporting
confidence: 87%
“…In such situation, the cathode geometry configuration is one of the possibilities that can improve the plasma parameters in terms of self-bias voltage (V dc ), electron density (n e ) and electron temperature (T e ), etc. [12][13][14]. In this sense, hollow and multi-hollow (H and MH) cathodes were proposed to be utilized as a light source [15], active media for gas lasers [16], sources of electrons [17], or for thin films deposition and large area surface treatment [18][19][20], and recently for the treatment of nanoparticles, plasma polymerization and nanocomposite fabrication [21].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of low T e may be brought with the secondary electrons in the grooves, which are generated by accelerated electron in the sheath region on the HC. 7) On the other hand, the decrease in the effect of high n e becomes large. The n e of the MHC is about 0.55 times that of the HC at the center.…”
Section: Hc Effect On Mhc Dischargementioning
confidence: 99%
“…4) The RF discharge with the use of the tapered shape HC has been studied in our laboratory, and the realization of uniform plasma has been experimentally demonstrated. [4][5][6][7] Also, we successfully produced dense plasma (10 17 m À3 ) and low temperature (1.7 eV) by RF (13.56 MHz) discharge with the use of HC. 7) In the case of the HC electrode, it is confirmed that the effect of HC discharge was maximum around the gas pressure p ¼ 8:35 Pa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation